Double-Bundle Posterior Cruciate Ligament Reconstruction Using Superficial Quadriceps and Semitendinosus Tendon Autografts - Ricardo de Paula L. Cury, M.D., Ph.D.; Viktor Nelson M. Correa, M.D.; Rafael Romano Rahal, M.D.; Alfredo dos S. Netto, M.D., M.Sc.; Victor Marquês de Oliveira, M.D., Ph.D.; Marcos Barbieri Mestriner, M.D., M.Sc. (Arthroscopy Techniques, 2025)
Posterior cruciate ligament (PCL) injuries are an important cause of knee instability. Recent advancements in understanding PCL anatomy and biomechanics have significantly improved surgical approaches. Double-bundle reconstruction, targeting the anterolateral and posteromedial bundles, has shown superior outcomes in restoring both subjective knee stability and objective biomechanics. However, the reliance on allografts for this procedure limits its feasibility in certain settings, driving the need for viable autologous graft alternatives that eliminate dependence on tissue banks. This study describes a double-bundle PCL reconstruction technique using autologous grafts: the superficial quadriceps (rectus femoris) for the anterolateral bundle and the semitendinosus for the posteromedial bundle.